2017
DOI: 10.1093/humrep/dex224
|View full text |Cite
|
Sign up to set email alerts
|

Unexplained recurrent miscarriages are associated with an aberrant sperm protamine mRNA content

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…In line with our findings, Rogenhofer et al [45] recently conducted an observational study and reported significant differences in PMN1 and PMN2 mRNA levels and the ratio of PMN1 to PMN2 mRNA between couples with recurrent miscarriages and healthy controls (p< 0.01). Despite the small sample size and ambiguity regarding the precise mechanism, they suggested that the levels of protamine gene expression in spermatozoa were not only essential for successful fertilization, but also for appropriate early embryo development [45]. In contrast, Torregrosa et al [46] reported no relationship between PMN2 gene expression and sperm DNA integrity.…”
Section: Discussionsupporting
confidence: 92%
“…In line with our findings, Rogenhofer et al [45] recently conducted an observational study and reported significant differences in PMN1 and PMN2 mRNA levels and the ratio of PMN1 to PMN2 mRNA between couples with recurrent miscarriages and healthy controls (p< 0.01). Despite the small sample size and ambiguity regarding the precise mechanism, they suggested that the levels of protamine gene expression in spermatozoa were not only essential for successful fertilization, but also for appropriate early embryo development [45]. In contrast, Torregrosa et al [46] reported no relationship between PMN2 gene expression and sperm DNA integrity.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, ICSI with testicular sperm from Tnp1 −/− Tnp2 +/− males yielded higher implantation rates and more offspring than obtained by ICSI of Tnp1 −/− Tnp2 +/− cauda epididymal sperm [88]. In men, impaired sperm protamination is associated with recurrent miscarriages [89] and decreased fertilization rates in ART programs [23][24][25]. Thus, in light of the molecular mechanism provided in this study, ICSI with testicular sperm presents as only treatment option for subfertile men with impaired protamination and severe DNA fragmentation.…”
Section: Discussionmentioning
confidence: 93%
“…54 Furthermore, a recent study by Rogenhofer et al demonstrated that P1 and P2 mRNA levels as well as the ratio of these two protamines were significantly different in male partners of women with unexplained recurrent pregnancy loss compared with healthy control men and subfertile couples undergoing in vitro fertilization/intracytoplasmic sperm injection. 55 Based on the current body of evidence, we believe we can hypothesize that sperm epigenetics impact embryo development and alterations can be implicated in pregnancy loss. We await further studies on this idea.…”
Section: Miscarriagesmentioning
confidence: 99%